Determinant Of Financial Performance in Indonesia - Dyah Ayu Ambarwati; Diah Ayu Susanti (Jurnal Ekuilnomi, 2026)
The study aims to evaluate the effect of green accounting implementation, environmental performance, and capital structure on the financial performance of companies engaged in the basic materials sector listed on the Indonesia Stock Exchange (IDX) in the period 2020-2024. This study is quantitative in nature. The population in this study consists of basic material companies listed on the Indonesia Stock Exchange for the period 2020-2024. The sample selection method used was purposive sampling with a total sample of 157. The data analysis technique used in the study was panel data analysis using Eviews 12. The study results show that green accounting and environmental performance do not affect financial performance. On the other hand, capital structure negatively affects financial performance